Dangerous Memories: Women Resisting Structures of Power, Possession, and Violence - Marilyn McKinley Parrish (Adult Education Research Conference, 2004)
As a result of involvement with the Catholic Worker movement, women learned to see the world in a new way, developing authentic spirituality, practicing nonviolent resistance to American cultural values, and trusting personal conscience as a guide for involvement in social justice issues.